An alternative to the use of animals to teach diabetes mellitus - Basso, Paulo José (American Physiological Society, 2014)
We developed an alternative approach to teach diabetes mellitus in our practical classes, replacing laboratory animals. We used custom rats made of cloth, which have a ventral zipper that allows stuffing with glass marbles to reach different weights. Three mock rats per group were placed into metabolic cages with real food and water and with test tubes containing artificial urine, simulating a sample collection of 24 h. For each cage, we also provided other test tubes with artificial blood and urine, simulating different levels of hyperglycemia. The artificial “diabetic” urine contained different amounts of anhydrous glucose and acetone to simulate two different levels of glycosuria and ketonuria. The simulated urine of a nondiabetic rat was prepared without the addition of glucose or acetone. An Accu-Chek system is used to analyze glycemia, and glycosuria and ketonuria intensity were analyzed by means of a Urocolor bioassay. In the laboratory classroom, students were told that they would receive three rats to find out which one has type 1 or type 2 diabetes mellitus. To do so, they had to weigh the animals, quantify the water and food ingestion, and analyze the artificial blood and urine for glycemia, glycosuria, and ketonuria. Only at the end of class did we reveal that the urine and blood were artificial. Students were instructed to plot the data in a table, discuss the results within their group, and write an individual report. We have already used this practical class with 300 students, without a single student refusing to participate.